Radioactivity and Mineralogy of Placer Concentrates from the Wiseman and Chandalar Districts, Upper Yukon Region, Northeastern Alaska - White, Max Gregg (United States. Government Printing Office., 1952)
From introduction: The purpose of this report is to present the results of the radiometric and mineralogic study of 19 samples from the Wiseman and Chandalar districts which are available in the Geological Survey's Alaskan collections. This work was done on behalf of the Division of Raw Materials of the U. S. Atomic Energy Commission.